Dying for a canape: the welfare implications associated with both traditional and “ethical” production of caviar from sturgeon - Lambert, Helen; Emam, Wasseem (Frontiers in Animal Science, 2024)
The farming of sturgeon to produce caviar is increasing globally, even though little is known about the welfare implications of aquaculture for these unique, long-living, and large animals. The use of nonlethal methods for egg harvesting is increasing as these methods are thought to offer a more ethical alternative to traditional methods where the female is killed. However, these 'nonlethal' methods raise significant welfare concerns including routine handling, surgical procedures, and painful procedures, and could potentially perpetuate suffering. Consequently, there is an urgent need for significant exploration and research into this field.This review presents and discusses some of the welfare concerns associated with producing caviar from sturgeon, including the traditional and nonlethal methods of egg harvesting and the concerns associated with rearing them in aquaculture systems. It concludes in stating that the welfare issues involved with nonlethal caviar production are too sizeable to warrant its description as an 'ethical or humane' alternative to traditional caviar production.Wild populations of sturgeon have declined as a result of both legal and illegal overfishing and significant habitat fragmentation and loss (